ANALISIS EKONOMI RUMAHTANGGA PENGUSAHA AGROINDUSTRI GULA KELAPA DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Nina Sawitri; Djaimi Bakce; Susy Edwina (Fakultas Pertanian, Universitas Riau, 2015)
This study aims to: (1) analysis the factors affecting production, allocation of work time, income and household expenditure coconut sugar agro-industry entrepreneurs. (2) analysis the impact of changes in economic policy related to the development of coconut sugar agro-industry to the economic decision-making household. Econometric approach with simultaneous equation models were analyzed by Two Stages Least Square method. The results showed that: (1) coconut sugar production is affected by the allocation of working time on coconut sugar agro-industry businesses. (2) The allocation of working time on the business affected by the age of the entrepreneur and the availability of capital. (3) The allocation of family labor time and the availability of capital is the main factor that determines the changes in household income entrepreneurs. (4) Household expenditure consists of consumption of food, non-food consumption, education, investment, leisure and savings. Consumption of food, non-food consumption, investment, leisure and savings are affected by household income coconut sugar agro-industry businessmen, while education is affected by a number of school children. (5) The policy of increasing the price of coconut sugar and increased allocation of working time have positive impact on the household economy, while the increase in wage costs have negative impact on the household economy. These results indicate that to increase the income of the coconut sugar agro-industry enterprises can be done: (1) Increase the allocation of working time on coconut sugar agro-industry effort to reduce the leisure. (2) Increase the accessibility of capital through government assistance or banks with low-interest credits.